Empoderamento das mulheres nas feiras agroecológicas da região metropolitana de João Pessoa – PB - Gomes, Josileide Carmem Belo (2024)
Over the years, society has presented a high level of inequalities in various aspects, especially between men and women, such as in work relationships, whether in activities carried out at home or tasks performed in work spaces. For this reason, inserted in a patriarchal environment, where sometimes women were born with their destinies already mapped out, and their entire lives were focused on learning how to take care of children, husbands and household chores, they were not given the opportunity to learn other things. The present research aimed to analyze the perception of women living in rural areas about their insertion in work spaces in the countryside and open markets, and to identify the decision-making processes of farmers linked to the networks of agroecological fairs existing in the metropolitan region of João Pessoa. The study was developed with family farmers linked to three associations: Ecovárzea, Ecocap and Ecosul, these associations are integral parts of the network of agroecological fairs in the metropolitan region of João Pessoa-PB. Data collection took place through field visits, questionnaire application, conversations and observations of the environment. In all fairs, two qualitative and quantitative questionnaires were applied. In the quantitative questionnaire, objective questions were also used on a scale from 0 (zero) to 5 (five), where the number 0 refers to "does not contribute" and the number 5 "fully contributes". Descriptive analysis and SAS statistical software were used for data processing. According to the results, the frequency of men at fairs is higher than women. However, the majority of women have a higher frequency of autonomy in matters related to home and child care. The productive practices developed in the family settlements are agroecological, in addition to contributing to the preservation of the environment, it provides healthy food. And such practices happen with female participation. Although there are divisions of labor, since some activities continue to be developed mostly by men, there is a progressive advance in the participation of women in decision-making. The presence of gender inequalities, invisibility of jobs was observed, an example is animal husbandry and the absence of power in decision-making, in issues that have historically been assigned to men. Therefore, the fair is a space in which everyone, men and women, work and collaborate collectively for the development of actions aimed at strengthening the participation of the family nucleus. And with regard to women, the fair is a special and meaningful space, where they insert themselves in the labor market, help with family income and work with perspectives of constant development of female protagonism and empowerment.